The Impact of Government Regulation Number 25 of 2024 on Political and Environmental Sustainability: A Case Study of the Granting of Mining Business Licenses to Nahdlatul Ulama and Muhammadiyah - Rohmah, Nazila Lailatur (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2024)
This research aims to analyze the effect of Government Regulation Number 25 of 2024 on the Amendment to Regulation Number 96 of 2021 on political and economic stability in Indonesia, focusing on a case study of the granting of mining licenses to Nahdlatul Ulama (NU) and Muhammadiyah social organizations. This government regulation was issued as part of the government's efforts to increase investment and economic growth, but this has implications for political and environmental stability in Indonesia. So that it has various impacts, both positive and negative impacts. The research method used is qualitative with case study analysis with a political environment approach. Data was obtained through analyzing related documents, previous research articles, and analyzing social media that discussed this issue in depth. The results show that the granting of mining licenses to Nahdlatul Ulama and Muhammadiyah has a significant impact on political dynamics in Indonesia. On the one hand, this step strengthens political support for the government from both organizations. However, on the other hand, there are potential conflicts of interest and dissatisfaction from other community groups, which can disrupt political stability. From an environmental perspective, the granting of this license has the potential to create a risk of environmental damage. The conclusion of this study emphasizes the importance of balancing political, economic and environmental interests in the implementation of government policies, as well as the need for public oversight and involvement in the decision-making process